Improving Hand-Eye Coordination Abilities Through Leaf-Rolling Activities at DWP 2 Bayem Kasembon Malang Kindergarten - Andriani; Ayu Asmah; Rina Wijayanti (CV Edujavare Publishing, 2026)
Fine motor development in early childhood involves the control of small muscles, and the ability to perform more precise and detailed movements. One of the scopes is hand-eye coordination. Efforts to facilitate the development of hand-eye coordination must be carried out with appropriate activities. The problems in DWP 2 Kindergarten, Bayem, Kasembon, Malang indicate that hand-eye coordination skills have not shown completeness. One of the contributing factors is the lack of stimulus in these skills. The purpose of this study is to determine the improvement of hand-eye coordination through stringing. This study uses Class Action Research (PTK) which is implemented through four stages, namely planning, action, observation and reflection. Data analysis techniques use observation. The implementation of the study in DWP 2 Kindergarten, Kesamben, Malang, with a total of 10 students. Observation cycle I showed results of 60% less than the completeness value, cycle II showed results of 80% and has met the completeness. It can be concluded that eye-hand coordination can be improved through stringing activities.